EUS-guided gallbladder drainage using a lumen-apposing self-expandable metal stent in patients with coagulopathy or anticoagulation therapy: a case series - Anderloni, Andrea; Attili, Fabia; Sferrazza, Alessandro; Rimbaș, Mihai; Costamagna, Guido; Repici, Alessandro; Larghi, Alberto (Endoscopy International Open, 2017)
Background and study aims We report our experience in endoscopic ultrasound-guided gallbladder drainage performed emergently in 4 prohibitive surgical risk patients with concurrent coagulopathy or on anticoagulant therapy using an electrocautery enhanced lumen apposing self expanding metal stent (LA-SEMS).